Approaches to the notion of "ambition" in the Paris Agreement: Perspectives for Chile - Urzúa Guerrero, Isaías; Jiménez Blasco, Guadalupe (Latin American Journal of Trade Policy, 2020)
The notion of "ambition" plays a preponderant role within the rules of the Paris Agreement, in particular, regarding the progressive updating of National Determined Contributions (NDC). However, this concept does not yet have sufficient clarity and distinction to be able to serve as a trulyguiding directive in the formulation of Chile's new contributions. That is why we try to deliver some guidance from the practice of climate negotiations and International Law. We also offer a brief orientation regarding the consequences that this reading would have for Chile when formulating its new NDC.